Frequency response of late-season 'Valencia' orange to selective harvesting by vibration for juice industry. (March 2017) - Castro-Garcia, S.; Blanco-Roldán, G.L.; Ferguson, Louise; González-Sánchez, E.J.; Gil-Ribes, J.A.
Abstract : Citrus mechanical harvesting has been investigated since the 1960's. Even though mechanical harvesting could significantly lower production costs, the implementation by the private sector has been slow. The current harvesting technologies detach the fruits with trunk, canopy or branch vibration. For late-season sweet orange varieties which simultaneously bear mature fruit, immature fruitlets and flowers, shaker harvesting decreases the subsequent year's yield. This study, investigated the frequency response of mature fruits and immature fruitlets to determine the optimum frequency range for an efficient and selective harvest. Laboratory vibration transmission tests were conducted with 14 branches bearing 76 mature fruits and 151 immature 'Valencia' fruitlets. The fruit and branch response to the forced vibration was measured by several sets of five triaxial accelerometers with a dynamic signal analyser. Three frequency ranges with the highest vibration transmission values were identified for mechanical harvesting lower than 10 Hz. The first frequency range (1.5–2.5 Hz) corresponded best with the most efficient vibration transmission, involving more than 90% of fruit. The second frequency range (4.5–5 Hz) successfully discriminated between mature fruit and immature fruitlets. In this frequency range, 53.4% of mature fruit amplified the acceleration a mean value of 2.2 times, while only 7.3% of immature fruitlets amplified the acceleration with a mean value of 4.4 times. The third frequency range (7–8 Hz) had the lowest vibration transmission value. The frequency response of mature citrus fruits, and their markedly higher fruit mass, were significant factors in efficient selective mechanical harvesting. Graphical abstract: Highlights: Vibration frequency values lower than 10 Hz are suitable for mechanical harvesting. Mature citrus fruits present a different response in 4.5–5 Hz range. Valencia orange fruit mass and maturity determine trunk shaker harvester frequency. Abscission agents are required for trunk shakers due to low vibration transmission.